Common Genetic Variants Contribute to Risk of Transposition of the Great Arteries. Issue 2 (21st January 2022) - Škorić-Milosavljević, Doris; Tadros, Rafik; Bosada, Fernanda M.; Tessadori, Federico; van Weerd, Jan Hendrik; Woudstra, Odilia I.; Tjong, Fleur V.Y.; Lahrouchi, Najim; Bajolle, Fanny; Cordell, Heather J.; Agopian, A.J.; Blue, Gillian M.; et al.
Abstract : Rationale: Dextro-transposition of the great arteries (D-TGA) is a severe congenital heart defect which affects approximately 1 in 4, 000 live births. While there are several reports of D-TGA patients with rare variants in individual genes, the majority of D-TGA cases remain genetically elusive. Familial recurrence patterns and the observation that most cases with D-TGA are sporadic suggest a polygenic inheritance for the disorder, yet this remains unexplored. Objective: We sought to study the role of common single nucleotide polymorphisms (SNPs) in risk for D-TGA. Methods and Results: We conducted a genome-wide association study in an international set of 1, 237 patients with D-TGA and identified a genome-wide significant susceptibility locus on chromosome 3p14.3, which was subsequently replicated in an independent case-control set (rs56219800, meta-analysis P=8.6x10 -10, OR=0.69 per C allele). SNP-based heritability analysis showed that 25% of variance in susceptibility to D-TGA may be explained by common variants. A genome-wide polygenic risk score derived from the discovery set was significantly associated to D-TGA in the replication set (P=4x10 -5 ). The genome-wide significant locus (3p14.3) co-localizes with a putative regulatory element that interacts with the promoter of WNT5A, which encodes the Wnt Family Member 5A protein known for its role in cardiac development in mice. We show that this element drives reporter gene activity in the developing heart of mice and zebrafish and is bound by the developmental transcription factor TBX20. We further demonstrate that TBX20 attenuates Wnt5a expression levels in the developing mouse heart. Conclusions: This work provides support for a polygenic architecture in D-TGA and identifies a susceptibility locus on chromosome 3p14.3 near WNT5A . Genomic and functional data support a causal role of WNT5A at the locus. Abstract : Supplemental Digital Content is available in the text.